A pore‐forming toxin enables Serratia a nonlytic egress from host cells. (23rd September 2016) - Di Venanzio, Gisela; Lazzaro, Martina; Morales, Enrique S.; Krapf, Darío; García Véscovi, Eleonora
Abstract: Several pathogens co‐opt host intracellular compartments to survive and replicate, and they thereafter disperse progeny to prosper in a new niche. Little is known about strategies displayed by Serratia marcescens to defeat immune responses and disseminate afterwards. Upon invasion of nonphagocytic cells, Serratia multiplies within autophagosome‐like vacuoles. These Serratia ‐containing vacuoles (SeCV) circumvent progression into acidic/degradative compartments, avoiding elimination. In this work, we show that ShlA pore‐forming toxin (PFT) commands Serratia escape from invaded cells. While ShlA‐dependent, Ca 2 + local increase was shown in SeCVs tight proximity, intracellular Ca 2 + sequestration prevented Serratia exit. Accordingly, a Ca 2 + surge rescued a ShlA‐deficient strain exit capacity, demonstrating that Ca 2 + mobilization is essential for egress. As opposed to wild‐type‐SeCV, the mutant strain‐vacuole was wrapped by actin filaments, showing that ShlA expression rearranges host actin. Moreover, alteration of actin polymerization hindered wild‐type Serratia escape, while increased intracellular Ca 2 + reorganized the mutant strain‐SeCV actin distribution, restoring wild‐type‐SeCV phenotype. Our results demonstrate that, by ShlA expression, Serratia triggers a Ca 2 + signal that reshapes cytoskeleton dynamics and ends up pushing the SeCV load out of the cell, in an exocytic‐like process. These results disclose that PFTs can be engaged in allowing bacteria to exit without compromising host cell integrity.